P442 The additional value of cytapheresis therapy in patients with severe ulcerative colitis treated with oral tacrolimus. (16th January 2018) - Takahashi, S; Colvin, M; Toyosawa, J; Ishida, M; Kagawa, T; Kuraoka, S; Aoyama, Y; Okamoto, K; Sakakihara, I; Izumikawa, K; Yamamoto, K; Tanaka, S; et al.
Abstract: Background: Oral tacrolimus therapy is an effective induction therapy for the remission of severe ulcerative colitis (UC), but it usually takes about 1 week to reach the therapeutic window. We evaluated the additional value of cytapheresis therapy to oral tacrolimus in patients with severe UC. Methods: We retrospectively evaluated 31 consecutive severe UC patients (Mayo score = 11, 12) who received oral tacrolimus therapy from April 2010 to June 2017 and were followed up for 120 days or longer. Three out of 31 patients who received biologics (anti-tumour necrosis factor agents) 120 days before or after the initiation of tacrolimus were excluded. Patients were divided into two groups (Tac group: received tacrolimus but not cytapheresis therapy, and Tac+CAP group: tacrolimus plus cytapheresis therapy) and the remission and response rates 120 days after the initiation of tacrolimus were compared between the two groups using partial Mayo score. Clinical response was defined with a decrease from baseline of at least 3 points in partial Mayo score. Clinical remission was defined as partial Mayo score equal to or <2 with no individual subscore >1. The overall adverse events were also compared between the two groups. Results: Twenty patients received tacrolimus but not cytapheresis therapy (Tac group) and eight patients received tacrolimus plus cytapheresis therapy (Tac+CAP group). In the Tac+CAP group, six patients received granulocyte and monocyte adsorption apheresis (GMA) and two patients received leukocytapheresis (LCAP). There were no significant differences between the two groups with respect to subject age, sex, disease duration, disease extent, disease severity, concomitant drugs, total administered steroid dose, C-reactive protein (CRP), white-cell count, haemoglobin, platelet count, albumin levels, initial dose of tacrolimus per body weight and tacrolimus trough level on Day 7. Eleven patients (55.0%) in the Tac group and eight patients (100%) in the Tac+CAP group achieved clinical response ( p = 0.12). Moreover, six patients (30.0%) in the Tac group and seven patients (87.5%) in the Tac+CAP group achieved clinical remission ( p = 0.020). The log-rank test revealed that remission rate was significantly higher in the Tac+CAP group compared with those in the Tac group ( p = 0.005). Epilepsy occurred in one Tac group patient and temporary renal dysfunction occurred in one Tac+CAP group patient. Conclusions: Cytapheresis therapy as an additional therapy to oral tacrolimus is effective in patients with severe ulcerative colitis.